2008
DOI: 10.1002/jmv.21161
|View full text |Cite
|
Sign up to set email alerts
|

GB virus type C infection in hemodialysis patients considering co‐infection with hepatitis C virus

Abstract: GB virus type C is a well-known viral agent with capability of infecting patients undergoing hemodialysis. Liver enzyme levels in infected individuals have been reported to remain within the normal range. Simultaneous infection of GBV-C and other viral agents may occur due to common routes of transmission. A total of 104 hemodialysis patients living in Tehran were included in this case-control study (53 patients with HCV infection, group I; and 51 with no HCV infection, group II). Diagnosis was made by detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
5
1
Order By: Relevance
“…Hossini-Moghaddam et al (2008) (southern Khorasan, Iran) described the prevalence of HGV RNA as 13.6% while the co-infection of HGV and HCV was 2% in patients on HD. In addition, Hossini-Moghaddam et al reported that the HGV genotypes 1a, 1b, 3a, and 3b were observed in patients on HD (27). However, in the current study, HGV genotype 2a was prominent in the patients on HD.…”
Section: Discussioncontrasting
confidence: 81%
“…Hossini-Moghaddam et al (2008) (southern Khorasan, Iran) described the prevalence of HGV RNA as 13.6% while the co-infection of HGV and HCV was 2% in patients on HD. In addition, Hossini-Moghaddam et al reported that the HGV genotypes 1a, 1b, 3a, and 3b were observed in patients on HD (27). However, in the current study, HGV genotype 2a was prominent in the patients on HD.…”
Section: Discussioncontrasting
confidence: 81%
“…The prevalence of GBV-C infection is greater among patients undergoing hemodialysis compared with blood donors or healthy individuals in the same region. In several countries, the reported prevalence of GBV-C markers ranged from 0.2-24.6% in blood donors (33)(34)(35) and ranged from 3.9-26.5% in patients undergoing hemodialysis (1)(2)(3)(4)(5)36). In the present study, the overall prevalence of GBV-C infection was 57.1%, which is similar to the prevalence of 55% reported in Yogyakarta in 1996 (7).…”
Section: Discussionsupporting
confidence: 77%
“…Patients undergoing hemodialysis are at increased risk of acquiring GB virus C (GBV-C) and torque teno virus (TTV; also known as transfusion transmitted virus) infection as a result of their impaired immune system and frequent contact with blood, blood products, equipment and surfaces contaminated with these viruses. A high prevalence of GBV-C infection in patients undergoing hemodialysis has previously been documented, with rates ranging from 3.9-26.5% in Iran, Egypt, Turkey and Brazil (1)(2)(3)(4)(5). Based on the results of two older studies, however, the prevalence in Indonesian patients undergoing hemodialysis is greater.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicate that the parental route of transmission may be an important method of viral transmission, though other routes ie sexual [43] and household contact [44] may also play a role in GBV-C epidemiology. The prevalence of GBV-C infection was 9% in a group of 64 hemodialysis patients from Caracas, Venezuela [45], 13.6%, all genotype 2, in a total of 104 hemodialysis patients living in Tehran [46]. In an Amerindian population from Venezuela a high prevalence of GBV-C genotype 3 was observed, ranging from 5% (9 out of 162) in the West to 25% (14 out of 56) in the South region of the country [45].…”
Section: Introductionmentioning
confidence: 90%